Hypertrophic Bone Spurs and Myositis Ossificans in Athletes: A Comparative Review of Clinical Features, Imaging, and Rehabilitation Approaches (Development Engineering Conferences Center Articles Database, 2025)
Background:Myositis ossificans (MO) and hypertrophic bone spurs (HS) are two distinct conditions involving abnormal bone formation, occasionally observed in athletes. While MO is well-documented in sports medicine literature, HS remains poorly characterized in athletic populations.Objective:To compare the clinical features, imaging findings, and rehabilitation outcomes of MO and HS in athletes, and to highlight the literature gap surrounding HS.Methods:This narrative review synthesizes current literature on MO and HS, focusing on etiology, presentation, imaging modalities, and treatment. Key studies addressing rehabilitation strategies for MO were analyzed, and available data on HS in the general population were reviewed for comparative purposes.Results:MO is consistently linked to acute muscle trauma and demonstrates favorable rehabilitation outcomes with conservative treatments such as shockwave therapy and guided physiotherapy. Conversely, no athlete-specific studies on HS were identified. Most available evidence on HS stems from general orthopedic cases, where physiotherapy modalities like ultrasound, TENS, and spa-based exercise have shown functional improvements.Conclusion:There is a substantial discrepancy in the evidence base for MO and HS in athletes. While MO management is well-established, HS remains underreported in sports medicine. Clinicians may cautiously extrapolate general HS rehabilitation strategies to athletic cases, although further research is needed to validate their effectiveness in this population.